In vitro and in vivo anthelmintic activity of Artemisia absinthium against gastrointestinal nematodes of free-grazing goats from Ayacucho, Peru - Flores Prado, Vania (2025)
Objective: The study assessed the anthelmintic activity of Artemisia absinthium ethanolic extract for controlling gastrointestinal nematodes in goats, both in vitro using infective larvae and in vivo in naturally infected goats under free-grazing conditions in the region of Ayacucho, Peru. Materials and Methods: For the in vitro assay, a larval motility inhibition test was performed on Trichostrongylus spp. infective larvae from goats using three different dilutions: 150, 175, and 200 mg/ml of the plant extract. In vivo efficacy was evaluated through the fecal egg count reduction test (FECRT), which was applied to 15 naturally infected Creole goats in one community. Animals were randomly assigned to 3 experimental groups and treated orally with 600 mg/kg of the plant extract. Fecal samples were collected directly from the rectum on days 0 (pre-treatment) and 7 and 15 post-treatment for egg count analysis. Results: In vitro results showed the highest inhibition of larval motility (81.79%) and larvicidal efficacy (82.2%) at the highest extract concentration (200 mg/ml). However, the in vivo results indicated that A. absinthium, at the concentration used, did not exhibit any significant effect on the FECRT. Conclusion: Although A. absinthium showed promising in vitro anthelmintic effects, the extract failed to demonstrate significant efficacy in vivo at the tested dose. Additionally, continuous monitoring of drugs in the region of study is strongly recommended based on the results obtained for albendazole.